Isolation and Characterization of Neural Progenitor Cells From Bone Marrow in Cell Replacement Therapy of Brain Injury - Bai, Wen-fang; Zhang, Yuling; Xu, Weicheng; Li, Weikun; Li, Meihui; Yuan, Fengying; Luo, Xun; Zhang, Mingsheng (Frontiers in Cellular Neuroscience, 2020)
Many studies supported that bone marrow mesenchymal stem cells (BM-MSCs) can differentiate into neural cells, but few researchers detected mature and function of nerve cells, especially in vivo study. Some researchers even suggested that BM-MSCs transplantation would not be able to differentiate into functional neural cells. To figure out the dispute, this study examined bone marrow-derived sphere-like cells, harvested via neural stem cell suspension culture, then identified as bone marrow derived neural progenitor cells (BM-NPCs) by finding the expression of neural progenitor cells genes and proteins, neural progenitor cells characteristic and nerve cell differentiation induced through both methods. Moreover, BM-NPCs transplantation showed long-term survival and improved the ethological and histological indexes of brain injury rats, demonstrating functional nervous cells differentiated from BM-NPCs. These in vitro and in vivo results confirmed BM-NPCs differentiating into mature and functional nerve cells. This study provided valuable experimental data for BM-NPCs, suggesting potential alternative treatment of central nervous injury disease.